Propulsion New Perspectives and Applications - Matsuuchi, Kazuo; Hasegawa, Hiroaki (IntechOpen, 2021)
Almost all animals move around frequently in space. Their aim is to walk and fly in search of food or to propagate their species. Thus, changing positions is important for creatures' survival and maintaining the environment. As such, this book examines movement with a focus on force and propulsion. Chapters cover topics including rocket engines, electric propulsion, mechanisms of force, and more.